Nascent Entrepreneurs in German Regions : Evidence from the Regional Entrepreneurship Monitor (REM) - Ingo Lückgen; Dirk Oberschachtsiek; Rolf Sternberg; Joachim Wagner (Institute for the Study of Labor (IZA), 2004)
Nascent entrepreneurs are people who are (alone or with others) actively engaged in creating a new venture and who expect to be the owner or part owner of this start-up. Given that newly founded firms are important for the economic development of nations and regions, and that nascent entrepreneurs are by definition important for the foundation of new firms, information about nascent entrepreneurs is important for understanding crucial aspects of the economy. The relevance of detailed information on nascent entrepreneurs at the regional level, and the lack of it for Germany, let us start the research project Regional Entrepreneurship Monitor (REM) Germany in 2000. As part of this project, we performed a representative survey of the adult population in 10 German regions, plus a survey and interviews with local experts in the field of entrepreneurship in 2001. A second wave followed in 2003. This paper summarizes our findings using data from these surveys and interviews.
Keywords: J23; 330; nascent entrepreneurs; Regional Entrepreneurship Monitor; Germany; Unternehmer; Unternehmensgründung; Region; Deutschland